New strategies in evaluation of therapeutic efficacy in fibromyalgia syndrome - Ozgocmen, S (Bentham Science Publ Ltd, 2006)
Fibromyalgia (FM) is continuing to be a challenging and confusing disorder for researchers and clinicians with its diverse symptoms, poorly understood etiology and pathophysiology. The use of multiple outcome variables reflecting the complexity of FM and co-morbid syndromes, makes it difficult to evaluate the efficacy or effectiveness of the treatment in clinical trials. Additionally researchers inevitably rely on patients' self reported outcome data, which is prone to error and bias. In this paper, new researches in the field of FM and practical issues on methodology of pain assessment (visual analogueue scales, paper or electronic diaries and compliance), core outcome domains in chronic pain assessment (IMMPACT recommendations), and advances in neuroimaging techniques like functional magnetic resonance imaging have been reviewed. Consequently, clinicians and researchers have various highly validated and adequate outcome domains to assess FM symptoms and new researches continue to add new valuable domains. Nevertheless the current problem is to conclude, which treatment works best for whom and which are the outcome domains suitable for FM patients or patients' subgroups with different prominent features. Standardised and appropriate core outcome domains for FM clinical trails will encourage more complete investigations, relevant outcome reporting and well-designed multicenter trials.
Keywords: fibromyalgia; core outcome domain; neuroimaging; diary; bias; pain